Komposisi media tanam berbasis polybag sebagai upaya pengoptimalan lahan sempit di Greenhouse Universitas Sulawesi Barat - Rahman, Abd.; Fatma, Sitti; Afingkan, Muliddia; Fitriah, Anis; Yusriadi, Muh. (Jurnal Tarreang: Tren Pengabdian Masyarakat Agrokompleks, 2024)
The problem of limited land is one of the obstacles in increasing agricultural commodity production. One way to overcome the problem of limited land is to implement sustainable agriculture. Efforts to increase chili production can be done in various ways, one of those is planting in polybags by adjusting the composition of the appropriate planting media. This is also the way of implementing sustainable agriculture. This community service aims to study the effect of the combination of the number of plants per polybag and the composition of the planting media on the growth and yield of chili plants (Capsicum sp.).